Blueberry Frost Protection Practices in Florida and Georgia - Tatiana Borisova; Elizabeth Conlan; Erick Smith; Mercy Olmstead; Jeffrey Williamson (EDIS)
This publication was developed to assist professionals working with blueberry producers to establish a benchmark for producers’ use of frost protection practices.  This benchmark can assist in developing outreach strategies educating producers about frost protection strategies, and it can also help measure changes in producers’ frost protection behavior over time.